Assessment of the implementation of energy needs and the participation of macroelements in the diet of professional athletes and amateur athletes training at the gym - Paula Marta Piątkowska; Bernadeta Szczepańska; Jacek J. Klawe (Kazimierz Wielki University, 2019)
Introduction. In sport, a key role in achieving success is the right training unit combined with the rational nutrition. Both professional and amateur sports require the delivery of an increased amount of energy and nutrients compared to people not making physical efforts. The aim of the work was to assess the energy value and the level of consumption of basic nutrients among professional athletes and amateurs at the gym. Material and methods. The research was conducted among 30 athletes who were at a sports camp in the "Zawisza" center and 30 amateur athletes training at the "Jatomi Fitness Drukarnia" gym in Bydgoszcz. The average age of the respondents was 20 ± 10.9 years. The energy value of the diet and the supply of macroelements were assessed on the basis of a 24-hour interview. Results. Energy supply for athletes accounted for 84.8% of the recommended norm of energy demand (women: 82.5%, men: 88.6%). The energy value of food intake consumed by amateur athletes training at the gym covered 81.1% of their 24-hour energy expenditure (women: 74.1%, men: 88.0%). The proportion of macronutrients in the diet of men and women training athletics was a well-defined level of the recommended standard: protein 92.9% and 85.8%, fats 126.3% and 117.7% and carbohydrates 77.9% and 72.8%, while for amateur trainers: 146.8% and 107.8% protein, 102.4% and 90.7% fats and 71.9% and 63.9% carbohydrates. Conclusions. An important element is the need for nutrition education of athletes. Nutritional intervention may increase the dietary awareness of people performing physical activity and help in proper balance of the menu.